2007
DOI: 10.1111/j.1365-2435.2007.01243.x
|View full text |Cite
|
Sign up to set email alerts
|

Testing the gravity hypothesis of sexual size dimorphism: are small males faster climbers?

Abstract: Summary1. Moya-Laraño et al . (2002; Evolution 56 , 420-425) showed that female-biased sexual size dimorphism is more pronounced in tree-dwelling spider species than in species inhabiting lower-lying substrates. They proposed the Gravity Hypothesis for sexual size dimorphism: small size should be advantageous for males in habitats where successful mate searching requires climbing, because mass-specific power and hence the speed of climbing against gravity, must decrease with increasing size. 2. Their biomecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
73
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(77 citation statements)
references
References 46 publications
3
73
1
Order By: Relevance
“…As our climbing trials revealed an optimal size for climbing speed at approximately 43 mg body mass (≈7.4 mm body length; according to Edwards, 1996 equation for a wide range of spider taxa; see the section), we predicted that in species that live in high‐habitats males should not evolve beyond this optimal size and hence pronounced SSD should become apparent with increasing size of the females – in contrast to species that live on the ground where male size is predicted to co‐evolve tightly with female size, as running speed on horizontal surfaces typically increases with size (Bauwens et al. , 1995; Brandt & Andrade, 2007a; Moya‐Laraño et al. , 2008).…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…As our climbing trials revealed an optimal size for climbing speed at approximately 43 mg body mass (≈7.4 mm body length; according to Edwards, 1996 equation for a wide range of spider taxa; see the section), we predicted that in species that live in high‐habitats males should not evolve beyond this optimal size and hence pronounced SSD should become apparent with increasing size of the females – in contrast to species that live on the ground where male size is predicted to co‐evolve tightly with female size, as running speed on horizontal surfaces typically increases with size (Bauwens et al. , 1995; Brandt & Andrade, 2007a; Moya‐Laraño et al. , 2008).…”
Section: Methodsmentioning
confidence: 97%
“…However, studies testing directly whether small males are faster climbers than large ones or have an advantage in scramble competition over access to females (i.e. find females first) have yielded mixed results: small males were favoured (Linn, 2001), no size effects were detected (Andrade, 2003; Foellmer & Fairbairn, 2005; Brandt & Andrade, 2007a; Kasumovic et al. , 2007), intermediate‐sized males were favoured (Vollrath, 1980) and even large males had an advantage (Foellmer & Fairbairn, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We calculated the intraclass correlation coefficient between the fastest and the next fastest trails for each assay of locomotor performance to determine repeatability of running and climbing performance [5,6] using SPSS 16.…”
Section: Methodsmentioning
confidence: 99%
“…, 2002), which states that extreme SSD with dwarf males could evolve and be maintained because smaller males climb faster and thus are better able to reach females that live high up in the vegetation. Although this hypothesis has been recently criticized (Brandt & Andrade, 2007a,b), additional evidence strongly suggests that although the relationship between climbing speed and body size is complex (i.e. positive below certain body size threshold and negative beyond the threshold), the gravity hypothesis can still accurately explain the evolution of extreme SSD (Foellmer & Moya‐Laraño, 2007; Moya‐Laraño et al.…”
Section: Discussionmentioning
confidence: 99%